Suboptimal care was frequent in severe child physical abuse cases and was mainly related to delayed diagnoses and ineffective secondary prevention. (26th February 2023) - Blangis, Flora; Malorey, David; Gras‐Le Guen, Christèle; Vabres, Nathalie; Picherot, Georges; Ricaud, Patricia; Chalumeau, Martin; Launay, Elise
Abstract: Aim: Our aim was to assess suboptimal care before a diagnosis of severe child physical abuse in western France. Methods: A confidential inquiry was carried out, based on children under 6 years of age who were hospitalised in the Nantes regional university hospital from 2016 to 2018. Two researchers retrospectively reviewed the medical records of all the children who were reported to the authorities for suspected severe child physical abuse. Two experts determined the optimality of care and identified the main categories of suboptimal care. Results: The median age of the 94 children included in the study was 8 months. A fifth of them had intra‐cranial injuries and a quarter had fractures. One child died and a third had severe sequelae at hospital discharge. Included children frequently (37%) received suboptimal care before the diagnosis of severe CPA and this fell into two categories: delayed diagnosis was experienced by 17% and ineffective secondary prevention by 22%. Conclusion: Suboptimal care for severe child physical abuse was frequent and fell into two categories: delayed diagnosis and ineffective secondary prevention. These results can help us to design corrective actions.